2020
DOI: 10.2196/17096
|View full text |Cite
|
Sign up to set email alerts
|

Combination of 3-Dimensional Virtual Reality and Hands-On Aromatherapy in Improving Institutionalized Older Adults’ Psychological Health: Quasi-Experimental Study

Abstract: Background In Taiwan, which has one of the most rapidly aging populations in the world, it is becoming increasingly critical to promote successful aging strategies that are effective, easily usable, and acceptable to institutionalized older adults. Although many practitioners and professionals have explored aromatherapy and identified its psychological benefits, the effectiveness of combining 3-dimensional (3D) virtual reality and hands-on aromatherapy remains unknown. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
(45 reference statements)
0
17
0
Order By: Relevance
“…According to Kirk [ 26 ], for an estimated effect size of 0.80, the approximate sample size required is 26 for each group when the power is set at 0.80 and type I error at 0.05. A previous 3D VR study yielded significant preintervention and postintervention improvements in psychological health with a similar sample size [ 19 ]. Another SVVR study with 32 participants in the experimental and control groups showed that providing childbirth education with SVVR resulted in superior learning performance [ 21 ].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…According to Kirk [ 26 ], for an estimated effect size of 0.80, the approximate sample size required is 26 for each group when the power is set at 0.80 and type I error at 0.05. A previous 3D VR study yielded significant preintervention and postintervention improvements in psychological health with a similar sample size [ 19 ]. Another SVVR study with 32 participants in the experimental and control groups showed that providing childbirth education with SVVR resulted in superior learning performance [ 21 ].…”
Section: Methodsmentioning
confidence: 98%
“…Furthermore, 3D VR promotes experiential and active learning, visualization and reification, learning in contexts impossible or difficult to experience in real life, motivation enhancement, collaboration fostering, adaptability, and evaluation and assessment. Previous studies also documented 3D VR as a useful intervention tool to train older adults [ 18 , 19 ]. Considering the success reported in the literature, this study projected the likelihood of the training effects on adult volunteers who helped prevent illegal drug use.…”
Section: Introductionmentioning
confidence: 99%
“…The authors recommended that future studies apply the OD prototype developed to disperse fragrance via air pump in synchronization with participant breath and virtual imagery via a head-mounted VR device (Oculus Rift). In a quasiexperimental trial by Cheng et al (2020), VR was combined with aromatherapy for elderly participants in a long-term care facility. Aromatherapy was combined with synchronized virtual nature imagery, such as dispersing orange fragrance while the participants picked oranges in VR.…”
Section: Olfactory Stimulus In Virtual Realitymentioning
confidence: 99%
“…Another limitation is the use of one fragrance blend, consisting primarily of lavender, developed to induce a calming response. Inclusion of different odors such as citrus scents (orange, lemon, and yuzu) and other fragrance blends may have yielded different results (Baron, 1990;Kiecolt-Glaser et al, 2008;Matsumoto et al, 2014;Cheng et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…A previous study [33] indicated that the most common purpose of horticultural therapy was to improve the mood of participants, followed by social interaction, stress reduction, and motor skill development. A systematic review [19] of randomized controlled trials on the effectiveness of horticultural therapy also found significant effects on mental health and behavioral disorders, such as dementia, schizophrenia, and depression and on palliative-care for patients with cancer.…”
Section: Generalmentioning
confidence: 99%